Pelatihan Pengukuran Biomotorik bagi Atlet Tinju Tingkat Sekolah Menengah Atas - Duhe, Edy Dharma Putra; Haryanto, Arief Ibnu; Horman, Jerry; Punu, Deddy (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service (PkM) aims to apply effective biomotor measurement techniques for high school-level boxing athletes to improve performance in the ring. The method of implementing this service used lectures, demonstrations, and cognitive tests targeting 9 boxing athletes and 2 coaches at SMAN 6 Gorontalo City. Lecture sessions covered strength, endurance, speed, agility, flexibility, balance, motor skills, body composition, explosive power, and functional tests. Demonstration sessions involved practical measurements using various tests to monitor athlete progress. The cognitive test results showed good understanding from the participants with an average of 83%, indicating increased knowledge about biomotors and their applications. This activity succeeded in improving participants' skills in evaluating and improving boxing performance, facilitating a more effective and highly competitive training program. The application of appropriate biomotor techniques could improve training programs and athlete performance.